Homophobic bullying and moral disengagement: when moral justification and guilty say “present” - Silva, Carla Beatriz Pereira da (2020)
This study sought to identify aspects of moral disengagement related to homophobic bullying experienced in the childhood and/or adolescence of university students. Through qualitative research, 14 college students from a city in the interior of the state of São Paulo were interviewed who declared themselves gay or lesbian. The group of participants was constituted through the snowball sampling technique. A script with guiding questions explored participants' perception of the mechanisms of moral disengagement as motivators for homophobic bullying experiences suffered during elementary and high school. The research data was analyzed through content analysis, thematic modality. The results obtained in this research showed that aggressors were morally disengaged and blame victims for feeling better, morally justifying their behavior. This study points out that anti-bullying interventions should consider the dissemination of content about human values, respect for diversity and the seriousness of aggressive behavior of children and adolescents.